RELIGIOUS TOURISM DEVELOPMENT MODEL IN BANYUWANGI - adytira rahman; Mochamad Ardi Setyawan (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
ABSTRACT This study aims to: 1) To identify and inventory the distribution of religious sites in Banyuwangi Regency; 2) Developing religious tourism models in Banyuwangi Regency; 3) Determine the right development strategy for religious tourism in Banyuwangi Regency. The data obtained was validated by using triangulation of data, researchers, theory and methodology. While the data analysis technique uses qualitative data analysis techniques which include data collection, data reduction, data presentation, and drawing verification. And the SWOT analysis which includes the preparation of the IFAS (Internal Factor Analysis Summary) matrix and the EFAS (External Factor Analysis Summary) matrix which is followed by the preparation of the SWOT matrix. This research is very important to be carried out on the basis of analysis, namely: 1) Banyuwangi stores many religious sites that have the potential to be developed as a tourist attraction; 2) Many religious sites are damaged and not maintained and the history of the document is not documented; 3) Religious sites in Banyuwangi Regency starting from the classical Hindu-Buda period to the Islamic period; 4) The existence of the phenomenon of Indonesian people has a unique motivation to travel that is to package a tour in the form of religious travel. The results showed that Banyuwangi has many religious sites that have the potential to be developed into religious tourism objects, including: 1) the Lingga and Yoni relics in Jambewangi; 2) Alaspurwo; 3) Rowu Bayu Site; 4) Ompak Songo; 5) Aningpatih Site; 6) Kawitan Sites; 7) Goa Site at Alaspurwo; 8) Image Worship Site; 9) Goa Maria; 10) Tomb of Sayid Yusuf; 11) Tomb of Mbah Dowo; 12) Tombs of the Regent of Banyuwangi; 13) Konco Hoo Tong Bio; 14) Tomb of Jogopati Rempeg; 15) Sri Tanjung Well; 16) Mbah Kopek's Grave; 17) Giri Salaka Temple. Keywords: Tourism, Religious, Integrated, Development